1980
DOI: 10.3354/meps002345
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in the Organic Carbon to Chlorophyll a Ratios for Estuarine Benthic Diatom Populations

Abstract: C/Chl-a ratios were determined for benthic diatom populations at 6 stations in the Ems estuary. For mixed field populations previous data are not available. Measurements were canied out over a period of nearly 3 years. The data were statistically analysed. Statistically significant differences in rat10 values were indicated within and between years. No indications were found for a statistically significant station effect upon the ratio values. The ratio values over the 3 year period investigated ranged from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(68 citation statements)
references
References 22 publications
3
64
1
Order By: Relevance
“…Detritus and empty frustules were abundant in the sample. However, we found a low phaeopigment content as compared to Chl a, and the C : Chl a ratio (52) is in the range of ratios reported for microphytobenthos (de Jonge 1980). Together, this information indicates that a great proportion of the material was alive.…”
Section: Resultssupporting
confidence: 60%
“…Detritus and empty frustules were abundant in the sample. However, we found a low phaeopigment content as compared to Chl a, and the C : Chl a ratio (52) is in the range of ratios reported for microphytobenthos (de Jonge 1980). Together, this information indicates that a great proportion of the material was alive.…”
Section: Resultssupporting
confidence: 60%
“…de Jonge (1980) suggested that when high C : Chl ratios are observed in benthic microalgal populations, it may reflect decreased diffusion of nutrients and increased excretion of mucilaginous products within the mat as a function of density. As diatom biomass increases, diffusion limitation within the mat intensifies and growth rate declines.…”
Section: Discussionmentioning
confidence: 99%
“…de Jonge (1980) concluded that the use of yearly C : Chl averages to estimate biomass could lead to errors of 34-50%.…”
mentioning
confidence: 99%
“…The annual range of microalgal biomass in the upper 0.5 cm of the sediment, estimated from an organic carbon:chlorophyll a ratio of 40 (de Jonge, 1980), varies from 227-305 mmol C m -2 in winter to 264-583 mmol C m -2 in summer. Thus, the standing crop only accounts for 10-20 % of the total organic carbon in the upper 0.5 cm at the coarse sand site (S), about 18 % at the fine sand site (A) and 7-14 % at the m u d d y sand site (M).…”
Section: Microbenthic Primary Production and Respirationmentioning
confidence: 99%